“À LUZ DO SOL” THEREZINHA ZERBINI E AS MOBILIZAÇÕES PELA ANISTIA NA DITADURA MILITAR: CONEXÕES, ESPIONAGEM E POLÍTICA (1975-1979) - Bernardes, Brenda Soares (2021)
Conceived by the opposition to the brazilian Military Dictatorship, mobilizations for amnesty took place between 1975 and 1979, culminating in the sanction of Law n. 6. 683/1979, the Amnesty Law. This dissertation covers the five years of the pro-amnesty campaign through the trajectory of Therezinha Zerbini (1928-2015), founder and leader of the first organized movement in the country, the Women's Movement for Amnesty (MFPA). Initially, the proposed amnesty should include exiles, political prisoners, and those whose political rights had been revoked. However, with the development of the movement, there was an expansion in the scope of the amnesty, understood as victory for human rights and democracy. This work argues that such mobilizations were possible because of the existence of several connections, of a temporal (generational) and spatial (transregional and transnational) nature, capable of bringing together people, ideas and objects in time and space. In the temporal (generational) dimension, the presence and absence of individuals capable of endowing amnesty of regional meaning and identity was identified. In the spatial dimension, there was an extensive circulation of people and ideas in Brazil and abroad. Therefore, the hypothesis holds that mobilizations transcend temporal, spatial and politically defined boundaries. It is argued that the mobilizations boosted the resumption of public spaces and democracy, by including it among their demands and by placing plurality and dissent as a condition of political life. Given the number of characters and places involved in the mobilizations, this work decided to analyze the campaign based on the actions of Therezinha Zerbini, one of the most relevant personalities to promote connections, through contacts, conferences, interviews and trips. From this itinerary, attention was paid to the weight of the regional dimension, whose marks were particularized according to realities and identities. Therefore, an attempt was made to locate the temporal and spatial connections promoted by Zerbini and, in general, by the Amnesty Movements, in particular the MFPA, the 1st of May Committee for Amnesty and the Brazilian Committee for Amnesty (CBA). Moreover, we tried to understand the Amnesty Movements as central social movements of the 1970s, observing their development and potential in the reconstruction of democracy in Brazil. When considering the sources used for this research, the collection of the National Information Service (SNI), the espionage exercised by the intelligence community on the Amnesty Movements and, especially, on Therezinha Zerbini, was analyzed through discourse analysis. Finally, attention was drawn to the protagonism of this character and the invisibility that befell the character in the post-1979 period.